Serum B sub(6) vitamers (pyridoxal 5'-phosphate, pyridoxal, and 4-pyridoxic acid) and pancreatic cancer risk: two nested case-control studies in Asian populations - Huang, Joyce Y; Butler, Lesley M; Midttun, Oeivind; Koh, Woon-Puay; Ueland, Per M; Wang, Renwei; Jin, Aizhen; Gao, Yu-Tang; Yuan, Jian-Min (Cancer causes & control, 2016)
Vitamin B sub(6) is an important enzymatic cofactor in pathways relevant for the development of pancreatic cancer. In order to evaluate vitamin B sub(6) as a preventive factor for pancreatic cancer, a biomarker approach is needed to overcome the limitations inherent in self-reported dietary information. To determine whether levels of serum B sub(6) vitamers, including pyridoxal 5'-phosphate (PLP), pyridoxal (PL), 4-pyridoxic acid (PA), and the PA/(PLP + PL) ratio (PAr), were associated with risk of pancreatic cancer, two nested case-control studies of 187 incident pancreatic cancer cases and 258 individually matched controls were conducted within two prospective cohorts of 81,501 participants in Shanghai, China, and Singapore. PLP, PL, and PA were quantified in pre-diagnostic serum samples. Odds ratios and 95% confidence intervals (CIs) were calculated using conditional logistic regression with adjustment for potential confounders. The median (5th-95th percentiles) concentrations of serum PLP among control subjects of the Shanghai and Singapore cohorts were 25.7 (10.0-91.7) nmol/L and 58.1 (20.8-563.0) nmol/L, respectively. In pooled analyses, high serum PLP was associated with a reduced risk of pancreatic cancer (P for trend = 0.048); the adjusted odds ratio for the highest category of PLP (>52.4 nmol/L) was 0.46 (95% CI 0.23, 0.92) compared to vitamin B sub(6) deficiency (<20 nmol/L). No associations were found for serum PL, PA, or PAr with pancreatic cancer risk. Higher concentrations of PLP may protect against the development of pancreatic cancer. The protective effect may be more apparent in populations with low concentrations of circulating vitamin B sub(6).